Navigating Maritime Digitalization: Socioeconomic and Organizational Perspectives on Technological Transformation - Pradita, Rizky Indra (Universitas Pattimura, 2025)
Maritime digitalization has become a transformative phenomenon that not only reshapes the operational landscape of the maritime industry but also has profound socioeconomic and organizational implications. This study aims to explore the impact of technological disruption on maritime management by examining digitalization dynamics through the lenses of disruptive innovation theory and the resource-based view. Employing a mixed-methods approach, this research integrates quantitative data analysis from industry reports with qualitative insights obtained through interviews and case studies of leading maritime enterprises. The findings reveal that digital technologies such as the Internet of Things (IoT), blockchain, and artificial intelligence significantly enhance operational efficiency and competitive positioning. However, the adoption of these technologies also presents complex challenges, including regulatory barriers, cybersecurity threats, and the need for workforce reskilling. This study proposes a conceptual model that illustrates the relationship between digital technologies, organizational capabilities, and market performance, providing a foundation for a deeper understanding of maritime digitalization dynamics. The novelty of this study lies in its approach, which not only highlights the technical aspects of digitalization but also examines how technological transformation affects the socioeconomic structure and work patterns within the maritime industry. The findings offer strategic recommendations for policymakers and maritime managers to navigate digital change effectively. Furthermore, this study contributes to the development of social sciences and humanities by emphasizing the interconnection between technological innovation, social change, and organizational adaptation in a historically conservative industry. Aligning technological investments with organizational strategies is a key factor in the successful digitalization of maritime operations, paving the way for future research on optimizing digital integration in maritime business management.